Penegakan Hukum terhadap Pelanggaran HAM di Pulau Rempang - Anisa Tri Ariyanti; Dodi Jaya Wardana (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This iresearch iexamines ithe isocial iand ieconomic iimpacts iof ithe iRempang iEco iCity idevelopment iproject ion iRempang iIsland, iBatam iCity, iwhich iinvolves ithe iBatam iBusiness iAgency iand ithe iprivate icompany iPT iMakmur iElok iGraha. iThe ibackground ito ithe iproblem iinvolves ia iconflict ibetween ilocal iresidents iand ijoint iforces ithat ioccurred ion iSeptember i7 i2023, iin iconnection iwith ia iland idispute iand ithe irelocation iof iresidents. iThe iresearch iobjective iis ito ianalyze ithis iconflict iin ia isocial, ieconomic iand ihuman irights icontext, iand iidentify iits iimplications ifor ilocal icommunities. iAnother iof ipurpose iis ito iexamine ithe ihuman irights ienforcement iin iIndonesian ilegal iand ipolitical isystem. iThe iresearch imethodology iincludes ifield idata icollection ithrough iobservations iand iinterviews, ias iwell ias ianalysis iof iproject-related idocuments. iThe iresearch iconclusion iis ithat ithis iconflict imust ibe iseen ias ia iserious iproblem iinvolving ivarious idimensions, iand iits iresolution irequires iattention ito ihuman irights, icommunity iparticipation.